Contemporary abstract art and its multidimensionality - Prokopovych, Tetiana; Avramenko, Dmytro; Kaleniuk, Olga; Lesyk-Bondaruk, Oksana; Vakhramieieva, Halyna (My University, 2020)
The article aims to discuss the author's concept of the phenomenon of abstract art. By absorbing all the achievements of humanity, art transforms and changes them, reflecting in its works the spirit of the time and the inner world of the artist living in this time. The development of science has actualized the issues of the relationship between ethical norms and artistic culture. The transformation of values, mentality, and perception of the world has led to cultural expression change. As a particular sphere of cultural life, art creates a need for new optics, a unique perspective of consideration, free from polar or eschatological assessments. The authors of the research article outline the fundamental aspects of the further development of contemporary art in the culture of postmodernism. The paper presents an exciting feature of modern art that influenced its development and public appreciation. In general, the article reveals the characteristics of cultural phenomena affecting contemporary art's formation and evolution.
Keywords: Abstract art; Multidimensional art; Cultural phenomena; Contemporary art; Forms of abstract image